The Impact of Gadget Use on Adolescents: a Literature Review - Vuriyanti, Mega; Rahmawati, Iis; Suhari, Suhari (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The use of gadgets by adolescents without balanced knowledge will impact health. The purpose of this study is to analyze the impact of gadgets on adolescents so that the impact of using gadgets can be prevented and minimized. This research method uses a literature review. Where in the process of searching for literature in this literature review using Pubmed, Scopus, Proquest, and Google Scholar databases with a range of published years 2019-2024. The search was done using several keywords "Impact" "Gadget" AND "Use". The results found 10 articles that show that excessive use of gadgets above the maximum use limit in adolescents causes various problems including physical health such as headaches, back pain, visual disturbances, neck pain, obesity, cognitive development disorders, and psychological health such as sleep disorders, loneliness, easy emotions and stress. Factors such as the lack of knowledge among adolescents about the time limit of gadget use, teacher control when adolescents are in the school environment and lack of parental control over adolescents in the use of gadgets at home trigger the emergence of gadget use in adolescents above the time limit determined by WHO so that it will cause addiction and impact on adolescent health. Therefore, collaboration between adolescents, families, educational institutions and health institutions is needed to prevent and reduce the impact of gadget use on adolescents.  Keywords: Gadget Addiction, The Impact Of Teen Gadget Use, Teen Health